2013
DOI: 10.1155/2013/108951
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effect of Continuous Venovenous Hemofiltration during Sepsis: Preliminary Data

Abstract: Introduction. Severe sepsis and septic shock are the primary causes of multiple organ dysfunction syndrome (MODS), which is the most frequent cause of death in intensive care unit patients. Many pro- and anti-inflammatory mediators, such as interleukin-6 (IL-6), play a strategic role in septic syndrome. Continuous renal replacement therapy (CRRT) removes in a nonselective way pro- and anti-inflammatory mediators. Objective. To investigate the effects of continuous venovenous hemofiltration (CVVH) as an immunom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…While treatment of infection with antibiotics is well established [ 3 ], control of systemic inflammation is equally important but difficult to achieve due to the extremely complicated nature of the reaction and numerous mediators involved. Haemofiltration has been suggested as beneficial in restoring immunohomeostasis [ 4 , 5 ]. Since the study of Ronco et al [ 6 ], demonstrating better intensive care patient survival with increased ultrafiltration rates of renal replacement therapy (RRT), high filtration volumes have been used in septic patients with the aim of controlling systemic inflammation and improving patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…While treatment of infection with antibiotics is well established [ 3 ], control of systemic inflammation is equally important but difficult to achieve due to the extremely complicated nature of the reaction and numerous mediators involved. Haemofiltration has been suggested as beneficial in restoring immunohomeostasis [ 4 , 5 ]. Since the study of Ronco et al [ 6 ], demonstrating better intensive care patient survival with increased ultrafiltration rates of renal replacement therapy (RRT), high filtration volumes have been used in septic patients with the aim of controlling systemic inflammation and improving patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…This study size is a limitation, as our trial was not adequately powered to detect differences between the 2 modalities in terms of cytokine clearance differences. However, it should be noted that similar studies done in the past that did note differences between the 2 modalities recruited similar numbers of patients [12,14,29]. Our sample size does not permit us to detect differences in a variety of outcomes including mortality and renal recovery.…”
Section: Discussionmentioning
confidence: 80%
“…Servillo et al [29] investigated the impact of high-flux CVVH on IL-6 gene expression in patients with AKI and septic shock. In this single group prospective observational study of 13 patients, 12 patients had a reduction in IL-6 mRNA after the first 12 h of CVVH with a subsequent increase after 24, 48, and 72 h. This study did not have a comparison group and as such it is difficult to determine if these changes in mRNA expression were due to CVVH or to the patients underlying sepsis [29]. In our study, while we did not measure mRNA expression, IL-6 levels consistently decreased over the first 48 h, regardless of the CRRT modality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the stressful state, such as severe trauma, shock, burn, or ICU, intestinal mucosa is in danger of aseptic injury, which increases the membrane permeability of the intestinal mucosa, leading to the dysfunction of the intestinal mucosa. The change of the membrane permeability is also the trigger causing distal organ injury . It was demonstrated that when the intestinal mucosa was impaired, the pro‐inflammatory cytokines from intestinal would flow into intestinal lymphatic system, rendering the systemic inflammatory response, and exacerbating further injury of tissues and organs, which was closely associated with MODS.…”
Section: Discussionmentioning
confidence: 99%